Kryzys migracyjny w Europie. Analiza zjawiska w mediach publicznych - Yuskiv, Bohdan M.; Юськів, Богдан Миколайович (Państwowa Wyższa Szkoła Zawodowa im. Jana Grodka w Sanoku, 2017)
The article deals with the problem Europe faced in 2015–2016, connected to unusually huge wave of illegal migrants. From the author’s pint of view, it’s the most important issue for the EU, called by various analysts and researchers the migrant crysis, to which the most appropriate name should be the EU migration policy crysis. It is proved by the end and sufficient results of the crysis. As for sufficient results, the author accounts them by: growing numbers of tmigrants coming to EU, appearing of the instability points, social and economic tensions within European societies connected to illegal migration, growing activity of terrorist gropus on European continent, growing regional international and intergovernmental tensions, conflict escalations in certain European regions in 2013–2015. Inability of the EU migaration system to cope with and react to the pressing and dynamic challenges, as well as building ability to avoid them in future, all are the end results of the crysis. This research proves that EU migration system is not aimed at complete and effective dealing with the crysis. Its characteristic features are lack of solidarity on the nations’ actions, their short-term character, lack of ability to predict future trends.
Migration crysis in Europe and its media coverage